Dynamic Audit Services for Outsourced Storages in Clouds - Mohan, K.J.Jagdish, Devi Parvathy (International Journal of Scientific Research and Management (IJSRM), 2017)
In cloud, the security issue in outsourced storage data is the difficult challenge. To overcome the problem, traditional approach developed a dynamic audit service for verifying the integrity of an untrusted and outsourced storage. An audit service is constructed based on the techniques, fragment structure, random sampling, and index-hash table, supporting provable updates to outsourced data and timely anomaly detection. The method based on probabilistic query and periodic verification for improving the performance of audit services. The audit service is performed by TPA monitoring. Sometimes the TPA may have chances to hide anomaly details to cloud users. To overcome the drawback, propose a dynamic audit service in the cloud. By the method it can dynamically audit the anomaly and send intimation to cloud user. So that it can secure the cloud storage data